Aplicação do método de pesquisa-ação na criação de protótipo de sistema web para clínicas de saúde - Silva, Vitor Gabriel do Nascimento (Departamento de Engenharias e Tecnologia - DETEC, 2026)
Healthcare clinics that use spreadsheets to manage their operations face challenges such as frequent errors, rework, wasted time, and fragmented information. This work proposes the prototyping of a web-based system, focusing on the User Interface (UI), in order to represent an integrated digital solution for automating administrative and financial processes. The proposal seeks to replace manual methods with a centralized and intuitive model, optimizing the clinics' routine. Among the proposed functionalities are the control of income and expenses, the generation of financial reports, and integration with patient, service, and scheduling modules. The Action Research methodology was used to develop the proposal. The expected outcome is a visual prototype representing a reliable, accessible, and efficient solution, especially useful for clinics that perform laboratory tests and require greater control and organization in their internal processes.
Application of the action research method in the creation of a web system prototype for health clinics
Keywords: ENGENHARIAS; Health clinics; Action research method; Prototype; Clínicas de saúde; Pesquisa-ação; Protótipo